2013
DOI: 10.1164/rccm.201208-1361oc
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclooxygenase-2–Prostaglandin E2Pathway Maintains Senescence of Chronic Obstructive Pulmonary Disease Fibroblasts

Abstract: PGE2 is a critical component of an amplifying and self-perpetuating circle inducing senescence and inflammation in COPD fibroblasts. Modulating the described PGE2 signaling pathway could provide a new basis to dampen senescence and senescence-associated inflammation in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 49 publications
5
74
2
Order By: Relevance
“…Senescent cells contribute to aging and age-related disease by generating a low-grade inflammatory state (42). Our results suggested that cellular senescence may promote inflammation, which is consistent with the findings of other studies demonstrating an increased production of IL-6 and IL-8 by senescent fibroblasts and epithelial cells (43,44). IL-6 and IL-8 may stimulate angiogenesis, enforce macrophage function and induce innate immune responses (45).…”
Section: Discussionsupporting
confidence: 90%
“…Senescent cells contribute to aging and age-related disease by generating a low-grade inflammatory state (42). Our results suggested that cellular senescence may promote inflammation, which is consistent with the findings of other studies demonstrating an increased production of IL-6 and IL-8 by senescent fibroblasts and epithelial cells (43,44). IL-6 and IL-8 may stimulate angiogenesis, enforce macrophage function and induce innate immune responses (45).…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest that FOXF1 may participate in compensatory mechanisms to fibrogenesis. Since FOXF1 is induced by the p53 family (42) and PGE 2 activates the p53 pathway in fibroblasts (9), it may be hypothesized that this pathway participated in FOXF1 repression by PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Senescent cells exhibit a complex phenotype characterized by permanent cell cycle arrest mediated by the p53 and/or p16/Rb pathways; increased cell size; altered cell morphology; resistance to apoptosis; altered gene expression, including β-galactosidase (β-Gal) upregulation; and a unique secretory phenotype known as the senescence-associated secretory phenotype (SASP) (8). We previously reported that a characteristic feature of COPD is the accumulation of senescent cells in the lung, which limits the potential for tissue renewal and contributes to chronic inflammation through the SASP (11)(12)(13). Whether cell senescence plays a causal role in the pathogenesis of COPD, however, remains unknown, and the mechanisms underlying cell senescence in COPD need to be clarified.…”
Section: Introductionmentioning
confidence: 99%